Avaliação de efeitos biológicos de antiinflamatórios derivados do ácido propiônico através de modelos experimentais em nível molecular e celular - Pereira, Márcia de Oliveira (2010)
Derivatives of propionic acid NSAIDs are irreversible inhibitors of cyclooxygenase enzyme widely used. The aim of this study was to evaluate, through different experimental models, biological effects of derivatives of propionic acid (fenoprofen, naproxen, ibuprofen and ketoprofen) in cellular and molecular level. The labeling of blood constituents with technetium-99m (99mTc) and morphological analysis of erythrocytes of blood of rats, as well as growth, survival of cultures of Escherichia coli (E. coli) and the assessment of bacterial plasmid electrophoretic profiles were models used for experimental evaluation of possible biological effects of antiinflammatory drugs. The results show that, in general, anti-inflammatory drugs evaluated were not able to alter the labeling of blood constituents with 99mTc, the morphology of red blood cells from blood of rats, as well as the growth of cultures of E. coli and the electrophoretic profile of plasmid DNA. However, naproxen appears to cytotoxic effect on bacterial cultures, plasmids and genotoxic effects in reducing the action of stannous chloride in cultures of E. coli. The use of experimental fast performance and low cost was important for assessment of biological effects, contributing to a better understanding of the properties of propionic acid derivatives studied. anti-inflammatory, blood constituents, technetium-99m, stannous chloride, Escherichia coli; DNA